Review on Moving Bed Biofilm Processes - Qiqi, Yang; Qiang, He; Ibrahim, Husham T. (Pakistan Journal of Nutrition, 2012)
The aim of this study is to present the Moving Bed Biofilm (MBB) technology as an alternative and successful method to treating different kinds of effluents under different conditions. In the past few years this technology has become more common and widely used in the world because the need for clean water is rapidly increasing as the world’s population grows by each year, so many wastewater treatment facilities are needed to being expanded to provide additional capacity with least possible cost. This review covered the most important processes on MBB such as basic treatment process, kinetics of biofilm, growth and detachment of particles, modeling of MBB and affecting of carrier type and filling ratio. The review also includes many relevant researches carried out at the laboratory and pilot scales.